Mencari Jejak Wiralodra Di Indramayu - Dini Nurlaelasari (Buletin Al-Turas, 2017)
Abstract This paper discusses how the establishment of Indramayu become a regency as now. Some previous papers about establishment of Indramayu is often associated with a figure named Wiralodra. To explore traces the establishment Indramayu became a regency there are a few things to consider. First, situation of Indramayu before becoming a regency. Second, about the lingkages between Wiralodra with the establishment of Indramayu as a regency. Third, the process of change in the administrative status of Indramayu. The methods used to discuss these issues are the historical method consists of heuristics, criticism, interpretation, and historiography. From this study, authors obtain about the condition of Indramayu before becoming a regency. Meanwhile lingkages between Wiralodra who had been believed to be founder Indramayu with establishment of Indramayu as a regency discussed by the historical fact. As well as the change of name and area before becoming Regency of Indramayu discussed by a government decision in various Staatsblad and Besluit.---Abstrak Tulisan ini membahas tentang bagaimana pembentukan Indramayu menjadi sebuah pusat pemerintahan setingkat kabupaten seperti sekarang. Dari beberapa karya tulis yang telah ada pembentukan Indramayu sering dikaitkan dengan tokoh bernama Wiralodra. Untuk menelusuri jejak-jejak pembentukan Indramayu menjadi sebuah kabupaten ada beberapa hal yang perlu diperhatikan. Pertama, keadaan Indramayu sebelum menjadi sebuah kabupaten. Kedua, tentang keterkaitan antara tokoh Wiralodra dengan pembentukan Indramayu sebagai sebuah kabupaten. Ketiga adalah proses perubahan status administratif Indramayu. Adapun metode yang digunakan untuk membahas persoalan tersebut adalah metode sejarah yang terdiri dari heuristik, kritik, interpretasi, dan historiografi. Dari penelitian ini penulis mendapatkan temuan-temuan tentang kondisi Indramayu sebelum menjadi sebuah kabupaten. Adapun keterkaitan antara tokoh Wiralodra yang selama ini diyakini sebagai pendiri Indramayu dengan pembentukan Indramayu sebagai sebuah kabupaten dibahas berdasarkan fakta historis yang penulis dapatkan. Begitupun perubahan nama dan luas wilayah sebelum menjadi Kabupaten Indramayu dibahas berdasarkan keputusan pemerintah dalam berbagai Staatsblad dan Besluit.DOI: 10.15408/al-turas.v23i1.4793